Visual Assessment and Genetic Distance Analysis of Gamma- Irradiated Lemon Leaf Mutants Developed Using the Leaf-Cut Method (MIST International Journal of Science and Technology, 2025)
Ionizing radiation, particularly gamma rays, is widely used to induce genetic mutations for improving morphological traits and enhancing genetic diversity in plants. In citrus plants, such mutations can be achieved by irradiating leaves and propagating the resulting mutants through vegetative methods. This study was conducted at the BINA research farm with the objective of developing Citrus limon mutants using gamma radiation and analyzing their morphological characteristics through visual inspection, alongside genetic diversity assessment using hierarchical clustering. A total of 400 fresh leaves were collected from the mother plant (BINA Lebu-1) and exposed to different doses of gamma radiation (0, 60, 80, and 100 Gy), divided into four treatment batches. The irradiated samples were planted in unit plots following a Randomized Complete Block Design (RCBD). Root and shoot development were monitored visually after 3 to 4 months. Maximum root length was observed at 100 Gy, the highest root quantity at 60 Gy, and the highest success rate at 80 Gy. After 7–8 months, mature plants were further assessed, and leaves were collected for genomic analysis. Genetic relationships among the different treatment groups were evaluated using a Dendrogram generated through simple hierarchical clustering. The results indicated clear genetic dissimilarities between irradiated (60, 80, and 100 Gy) and non-irradiated (0 Gy) plants, with the 100 Gy group showing the greatest genetic distance from the others. Due to time constraints, fruit production could not be observed. Nonetheless, the study demonstrates the effectiveness of combining visual inspection and genetic distance analysis in evaluating gamma-induced citrus mutants developed via the leaf-cut method.MIJST, V. 13,December 2025: 65-71https://doi.org/10.47981/j.mijst.13(02)2025.559(65-71)